2023
DOI: 10.1093/jee/toad101
|View full text |Cite
|
Sign up to set email alerts
|

Pear psylla and natural enemy thresholds for successful integrated pest management in pears

Abstract: Pear psylla, Cacopsylla pyricola (Förster), is the most economically challenging pest of commercial pears in Washington and Oregon, the top producers of pears in the United States. The objective of this study was to quantify economic injury levels and thresholds for pear psylla. We used the relationship between pear psylla adult and nymph densities, and fruit downgraded due to psylla honeydew marking to identify injury levels. We calculated economic injury levels using the cost of downgraded fruit and average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Therefore, as is typical for density-independent control [45], it is expected that they are more likely to prevent increases in pest populations, rather than decrease the abundance of already problematic pest populations [46]. This partially explains why earwigs, as an important part of the natural enemy complex of pear psylla in the Pacific Northwest, assist mostly in controlling a pest during their second and third generations [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, as is typical for density-independent control [45], it is expected that they are more likely to prevent increases in pest populations, rather than decrease the abundance of already problematic pest populations [46]. This partially explains why earwigs, as an important part of the natural enemy complex of pear psylla in the Pacific Northwest, assist mostly in controlling a pest during their second and third generations [19].…”
Section: Discussionmentioning
confidence: 99%
“…Overall numbers in the OR orchard were still very low even after two years of releases (seasonal average of one per trap at most), suggesting that yearly releases might still be needed to achieve thresholds for pest control. It has been suggested that greater than two earwigs per trap is correlated with the suppression of second-and third-generation pear psylla [19]. Another argument in favor of yearly releases in orchards with low earwig abundance is that due to their poor dispersal behavior-moving only up to 30 m per month [34]-earwigs are thought to slowly recolonize areas where they have been absent [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dislodged insects cling to the cloth and are counted. The threshold counts of psyllids on trays which indicate that treatment is necessary to manage russet are discussed in Nottingham et al (2022b) and DuPont et al (2023). A second method for monitoring the adult psyllid is with use of sticky cards.…”
Section: Pest Managementmentioning
confidence: 99%